Sensibilidad a la Histoplasmina en algunas localidades del Perú - Bouroncle Carreon, Alfonso (1955)
From studies Strrong, Darling and Rocha Lima, that the clinical characteristics and fungal origin of histoplasmosis are established, numerous studies have been conducted to understand the different aspects of both clinical and epidemiological pathogens such as disease, having, in time, clarified and clarified the concepts they had of this condition, both in terms of frequency forecast and distribution.